Contribution of 155Gd Mössbauer data to the study of the magnetic interaction in heterodinuclear 3d–Gd (3d = Cu, Ni) coordination complexes. Issue 20 (26th April 2019) - Ayabe, Takanari; Costes, Jean-Pierre; Vendier, Laure; Geist, Andreas; Takeda, Masuo; Takahashi, Masashi
Abstract : The observed 155 Gd Mössbauer isomer shifts of 3d–Gd complexes give an experimental proof for the participation of 5d Gd orbitals to the magnetic interaction in these 3d–Gd complexes. Abstract : The valence shell of the gadolinium element corresponds to 4f 7 5d 1 6s 2, so that the trivalent Gd III ion possesses free 5d and 6s orbitals. It has been previously shown by CASSCF methods that the 5d orbitals, along with the 6s Gd orbitals, which are expected to be unoccupied, present a slight spin density and that the magnetic behaviour of Cu II –Gd III complexes can only be reproduced if the 5d Gd orbitals are taken into account in the active space. 155 Gd Mössbauer isomer shifts of 3d–Gd complexes, L 1 CuGd(NO3 )3, L 1 NiGd(NO3 )3 ·acetone, L 2 Cu(acetone)Gd(NO3 )3, L 2 Ni(H2 O)2 Gd(NO3 )3 where L 1 and L 2 are hexadentate Schiff base ligand, are almost unchanged (0.62–0.64 mm s −1 relative to 155 Eu/SmPd3 source) though the values are slightly smaller than a typical ionic compound GdF3 (0.67 mm s −1 ). The very similar isomer shift values of the 3d–Gd complexes indicate that there is no change in the small electron density of the 6s orbital and that the spin delocalization or spin polarization concerns the 5d Gd orbitals, in agreement with the crystal structure and Mössbauer spectrum of the Gd complex of nitrogen-coordinating tridentate ligand Pr n TBP, [Gd(Pr n TBP)3 ](OTf)3 . Thus the observed 155 Gd Mössbauer isomer shifts of 3d–Gd complexes give an experimental proof for the participation of 5d Gd orbitals to the magnetic interaction in these 3d–Gd complexes.